Visual and anatomic outcomes of sustained single agent anti-VEGF treatment versus double anti-VEGF switching in the treatment of persistent diabetic macular edema. - Sorour, Osama A.; Liu, Keke.; Mehta, Nihaal.; Braun, Phillip.; Gendelman, Isaac.; Nassar, Elsayed.; Baumal, Caroline R.; Witkin, Andre J.; Duker, Jay S.; Waheed, Nadia K. (Tufts University. Tisch Library., 2020)
Keywords: Diabetic macular edema, Anti-VEGF, OCT, Diabetic retinopathy, Intravitreal.; Springer Open.